2006
DOI: 10.1158/0008-5472.can-05-2803
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of RAD51B Causes Centrosome Fragmentation and Aneuploidy in Human Cells

Abstract: The Rad51-like proteins, Rad51B, Rad51C, Rad51D, XRCC2, and XRCC3, have been shown to form two distinct complexes and seem to assist Rad51 in the early stages of homologous recombination. Although these proteins share sequence similarity with Rad51, they do not show functional redundancy. Among them, Rad51B is unique in that the gene maps to the human chromosome 14q23-24, the region frequently involved in balanced chromosome translocations in benign tumors particularly in uterine leiomyomas. Despite accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…1). Consistent with previous studies (39,44), the RAD51B knockdown MCF7 cells exhibited a comparable reduction in RAD51 foci formation on the DSB sites after ionizing radiation (Fig. 1, B and C).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…1). Consistent with previous studies (39,44), the RAD51B knockdown MCF7 cells exhibited a comparable reduction in RAD51 foci formation on the DSB sites after ionizing radiation (Fig. 1, B and C).…”
Section: Resultssupporting
confidence: 91%
“…RAD51B-deficient cells are hypersensitive to DSB-inducing agents, such as cisplatin, mitomycin C (MMC), and ␥-rays, indicating that the RAD51B protein is involved in the HRR pathway (39 -44). Genetic experiments revealed that RAD51B-deficient cells exhibited impaired RAD51 assembly onto DSB sites (39,44), suggesting that the RAD51B protein functions in the early stage of the HRR pathway. Biochemical experiments also suggested that the RAD51B protein participates in the early to late stages of the HRR pathway (45)(46)(47).…”
mentioning
confidence: 99%
“…However, 48 hours after irradiation, the proportion of cells with fragmented centrosomes was similar to the level observed for both unirradiated cell lines. Taken together, these results indicate that depletion of PARG exacerbates the centrosome amplification and fragmentation that has been already described in irradiated cells, in cells deficient in proteins involved in DSB repair or in cells overexpressing PARP3 and treated with an alkylating agent (Augustin et al, 2003;Date et al, 2006;Griffin et al, 2000).…”
Section: Irradiated Parg Kd Cells Display Centrosomal Abnormalitiessupporting
confidence: 77%
“…A growing body of evidence suggests that aneuploidy is often caused by chromosomal instability during mitosis (3,4), which may result from an improper duplication of centrosomes. The centrosome organizes the spindles for the separation of chromosomes during mitosis, and the presence of more than two centrosomes in a cell can result in lost chromosomes or in an excess number of chromosomes (2,5).…”
Section: Introductionmentioning
confidence: 99%